Strategi Pembelajaran sebagai Kunci Mendorong Hasil Belajar Siswa - Sifana Alqorana; Putri Sidahtilla Umma; Rahma Dini Pratiwi; Sani Safitri; Rani Oktapiani (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
Effective learning requires teachers to be able to select and apply innovative learning strategies so that the learning process becomes more meaningful for students. Innovation in learning strategies is important because it can increase student engagement, motivation, and learning outcomes through approaches that are tailored to their needs and characteristics. This study aims to describe the role of innovation in learning strategies as the key to encouraging improved student learning outcomes. The method used is a qualitative literature study by collecting and analyzing various literature sources in the form of books, journals, and relevant scientific documents. The findings show that innovative learning strategies, such as problem-based, collaborative, contextual learning, and the use of technology, can improve students' critical thinking, creativity, and active participation. In addition, strategies creatively designed by teachers can create a more engaging learning atmosphere and motivate students to achieve learning objectives. This study implies the importance of improving teacher competence in developing innovative learning strategies as an effort to achieve optimal learning outcomes.